(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Nature insensitive construction activities have obliterated the fate of life on Earth.Thus the thepresent paper on “BUILDING THE NATURE SENSITIVE WAY - A Review Of Approaches Of EcosystemReplacement And Restoration In Construction Sector “gainsimportance. This narrative review focusseson concepts of„ Ecosystem Replacement And Restoration‟. It aims at sensitization of mindsets ofconstruction sector stakeholders to opt for nature sensitive approaches in decision making. The studybuilds upon qualitative analysis of secondary data collected through literature review to exploreviablesolutions. The paper calls for further research for deeper technological insights and quantification ofimpacts.